2012
DOI: 10.1021/om300876b
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Dihydrogen Elimination from Cp*2Yb(4,5-diazafluorene)

Abstract: The reaction of 4,5-diazafluorene with Cp* 2 Yb(OEt 2 ), where Cp* is pentamethylcyclopentadienyl, affords the isolable adduct Cp* 2 Yb(4,5-diazafluorene) (1), which slowly eliminates H 2 to form Cp* 2 Yb(4,5-diazafluorenyl) (2); the net reaction is therefore 1 → 2 + H • . The ytterbium atom in 1 is shown to be intermediate valent by variable-temperature L III -edge X-ray absorption near-edge (XANES) spectroscopy, consistent with its low effective magnetic moment (μ eff ). The experimental studies are supporte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
80
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(84 citation statements)
references
References 20 publications
3
80
1
Order By: Relevance
“…15 These adducts also have an intense absorption around 900 nm, which was assigned to a f--f transition in Cp*2Yb(phen). 15 Although this transition is forbidden, its intensity is attributed to the formation of a ligand--to--metal charge transfer state, 1 LMCT, in which intensity is stolen. 15 The solution 1 H NMR spectra in C6D6 at 20 °C for the dime-thylphenanthroline adducts are listed and assigned in Table 5.…”
Section: Bond Cmentioning
confidence: 99%
See 1 more Smart Citation
“…15 These adducts also have an intense absorption around 900 nm, which was assigned to a f--f transition in Cp*2Yb(phen). 15 Although this transition is forbidden, its intensity is attributed to the formation of a ligand--to--metal charge transfer state, 1 LMCT, in which intensity is stolen. 15 The solution 1 H NMR spectra in C6D6 at 20 °C for the dime-thylphenanthroline adducts are listed and assigned in Table 5.…”
Section: Bond Cmentioning
confidence: 99%
“…Compound color m.p (°C) IR (cm --1 ) µ eff (300K) a) Cp * 2Yb (2, (1) deep purple 313--317 1622, 1592, 1505, 848 1.62 Cp * 2Yb(4,7--Me2phen) (2) deep purple 265--268 1622, 1577, 1520, 849 1.98 Cp * 2Yb (3,4,7, (3) dark brown 264--266 1611, 1567, 1518, 810 1.79 Cp * 2Yb (3,4,5,6,7, (4) dark brown 270--272 --1.67 Cp * 2Yb(2,9--Me2--4,7--Ph2phen) (5) dark purple 288--292 1622, 1569,1547, 880 2.05 [Cp * 2Yb(4,7--Me2phen)]I (6) gold yellow 214--218 1631, 1534, 1430, 728 4.44 Cp * 2Yb(5,6--Me2phen) 6 deep purple 285--287 1605, 1584, 1480, 804 3.68 a) In µB per Yb(III), calculated from a plot of χT vs T, where μeff = 2.828 (χT) ½ --at T = 300 K.…”
Section: Introductionmentioning
confidence: 99%
“…These very small isotropic shifts are to be compared to those found in the Cp* 2 Yb(3,3 0 -Me 2 bipy) 14 and 2 is likely to exhibit a similar electronic structure that is an intermediate-valent situation with a large contribution of the divalent resonance structure. In the solid state, the X-ray crystal structure exhibits a large torsion angle between the two phosphinine rings.…”
Section: Solution Nmr and Effective Momentsmentioning
confidence: 86%
“…2 On the other hand, Cp* 2 Yb(phen) has a triplet ground state. 14 In 2014, some of us described the steric influence of samarium complexes in this electron transfer event using bulky ligands such as Cp ttt (tris-tert-butylcyclopentadienyl) and have shown that the redox potential net value was to take cautiously when it comes to single electron transfer in lanthanides complexes. In bipyridine, the LUMO is of b 1 symmetry (C 2v label) and is of a 2 symmetry in phenanthroline.…”
Section: Introductionmentioning
confidence: 99%
“…The two open-shell singlets were calculated to be multiconfigurational and closely spaced, in agreement with the observed temperature dependence of the XANES and data, which were fit to a Boltzmann distribution. A mechanism for dihydrogen formation has been proposed on the basis of kinetic and labeling studies to involve the bimetallic complex (Cp * 2 Yb) 2 (4,5-diazafluorenyl) 2 , in which the heterocyclic amine ligands are joined by a carbon-carbon bond at C(9)-C(9 ) (Scheme 88) [63].…”
Section: Pentamethylcyclopentadienyl Compoundsmentioning
confidence: 99%